Feasibility and preliminary effects of a peer-led motivationally-embellished workplace walking intervention: A pilot cluster randomized trial (the START trial) - Thogersen-Ntoumani, Cecilie; Quested, Eleanor; Smith, B.S.; Nicholas, Joanna; McVeigh, Joanne; Fenton, S.A.M.; Stamatakis, E.; Parker, Sharon; Pereira, Gavin; Gucciardi, Daniel; Ntoumanis, Nikos (2020)
Walking interventions can be effective in increasing physical activity amongst physically inactive employees. However, despite their promising potential regarding sustainability and scalability, peer-led workplace walking interventions have not been tested. We evaluated a peer-led workplace group walking intervention designed to engage physically inactive employees. A 16-week pilot cluster randomized controlled trial consisted of enhanced (5 worksites; n = 50 participants) and minimal treatment (3 worksites; n = 47) conditions. All participants were provided with a Fitbit Zip and information on health benefits of walking. Enhanced treatment participants had access to a mobile phone app incorporating behavior change techniques, were trained on principles of autonomous motivation, and had a peer leader trained in a motivationally supportive communication style. Feasibility assessments included recruitment and drop-out rates, assessment completion rates, training acceptability (walkers and peer leaders), and intervention acceptability (walkers only). Outcomes assessed included movement-related behaviors (assessed via activPAL devices), cardio-metabolic risk factors, motivation to walk, and well-being, and these measures were taken at baseline and post-intervention. The results supported intervention feasibility. Preliminary efficacy evidence was mixed. Markers of cardio-metabolic risk improved in the enhanced treatment only. Autonomous motivation increased in both conditions. There were no changes in step counts, standing, and sitting time, or well-being. Further fine tuning is needed before a definitive RCT. Australian and New Zealand Clinical Trials Registry: ACTRN12618000807257.